Tinjauan Yuridis Terhadap Peralihan Hak Atas Tanah dalam Sengketa Jual Beli(Studi Kasus Putusan PN Karanganyar No.52/Pdt.G/2014.PN.Krg) - Widyaningsih, Indah, Shalman Al Farizi.S.H.,M.Kn (2017)
This study aims to determine the consideration of the judge in determining the verdict disputed land purchase is done by under the hands and to know the resistance of the certificate the name behind the decision No.52 / Pdt.G / 2014.PN.Krg. This study uses normative legal approach. Data collection techniques in this research is the study of literature and then analyzed by qualitative data analysis, which analyzes court rulings relating to the sale and purchase of land is done by hand under. These results indicate that (1) the judges declared invalid the transfer of land rights in the buying and selling is done by hand under (2) Karanganyar District Court's Decision No.52 / Pdt.G / 2014.PN.Krg used to do back the name of the certificate. Keywords: Transition, Purchase, Behind the Name